(untitled) (Texas Journal of Engineering and Technology, 2022)
This paper considers the “smart cities” phenomena as the digital transformation alternative for city governance similar to the digital transformation of enterprises. Therefore, in this paper, we propose to use the Enterprise Architecture (EA) methodology and relevant information systems by considering the city as a large organization. Suggested assessment procedure of government-specific EA tools uses customer experience ratings processed with fuzzy logic techniques.